Investigating the determinants of vocational education and economic development in digital age: A review from 2018-2023 - Li wei; Janice L. H. Nga; Imran A. Shahzad (International Journal of Religion, 2024)
Vocational education plays a crucial role in the development of individuals by providing them with the most essential skills. The crucial importance of vocational education necessitates support from various elements, including government policy and the educational aspect within the vocational school. However, higher vocational education and economic development in the digital age face several challenges, stemming from enrollment trends, policy interventions, labor market dynamics, and demographic shifts. This study provides a systematic review using PRISMA guidelines for addressing higher vocational education enrollment, policy interventions, labor market trends, and demographic factors that affect the integration of vocational education and economic development in the digital age. The initial phase involves the identification of a suitable source database, which may include prominent platforms such as Scopus, Google Scholar, or IEEE Xplore The findings of the study reveal that most students enrolling in higher vocational education recommend using hands-on training and practical skills that have been directly applicable to my current job in the IT industry. The program needs to focus on industry-relevant skills for the demands of the labor market. We also identifying and filling these research gaps could lead to a more comprehensive and critical understanding of vocational education. Vocational education programs can adapt to labor market trends by incorporating emerging technologies into their curricula, collaborating with industry experts to identify skill gaps, and offering continuing education courses to keep graduates up to date with the latest advancements. Finally, this study provides some recommendations for further studies.